Upaya Pengembangan Fisik Motorik Anak Usia Dini melalui Permainan Tradisional Ayam dan Musang - Dini Handayani; Sofia Ratna Awaliah Fitri; Saepul Milah (CV. Biha Cendekia, 2025)
Motor physical development is one of the fundamental aspects of early childhood growth. During the golden period, proper stimulation of this ability will have a significant impact on a child's motor skills in the future. One form of stimulation that can be provided is through traditional games. This article uses a literature study and observation method regarding the implementation of the “Chicken and Fox” game in children aged 5-6 years. Data were collected through observation of children's activities while playing, then analyzed based on gross motor development indicators. The analysis results indicate that this game can stimulate speed, strength, agility, coordination, and body balance. For example, running exercises the leg muscles, while the role of the 'Mother Hen' in protecting her chicks requires agility and coordination. Thus, the game 'Chicken and Fox' is an enjoyable as well as educational alternative to optimize the motor development of young children, and it aligns with local culture, enriching the stimulatory experiences for child development.